2003
DOI: 10.1002/ejoc.200390200
|View full text |Cite
|
Sign up to set email alerts
|

Domino [3+2] Cycloaddition/Annulation Reactions of β‐(2‐Aminophenyl)‐α,β‐ynones with Nitrile Oxides: Synthesis of Isoxazolo[4,5‐c]quinolines

Abstract: β‐(2‐Aminophenyl)‐α,β‐ynones react with nitrile oxides by domino [3+2] cycloaddition/annulation reactions giving rise to isoxazolo[4,5‐c]quinolines in satisfactory yields. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…According to our previous studies, [1][2][3][4][5] the present process can be explained as depicted in Scheme 3: regioselective 1,3-dipolar cycloaddition of nitrones 2 to α,β-ynones 1 results in the formation of alkenes 5, from which the quinoline nucleus is generated by condensation between the amino and carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our previous studies, [1][2][3][4][5] the present process can be explained as depicted in Scheme 3: regioselective 1,3-dipolar cycloaddition of nitrones 2 to α,β-ynones 1 results in the formation of alkenes 5, from which the quinoline nucleus is generated by condensation between the amino and carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] Moreover, we reported that sequential [2+2] cycloaddition of cycloalkanone enamines with 1 followed by cyclocondensation afforded quinolines cis-fused to different-sized carbocyclic rings. [4] In a related process, the reactions of 1 with azides [1] or nitrile oxides [5] resulted in the formation of quinoline derivatives cis-fused to heteroaromatic triazole or isoxazole rings. These synthetic methods can lead to the formation of polycyclic quinolines that are not otherwise easily available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] During the program we became interested in the synthesis of isoxazolo [4,3-c]quinolines. A literature survey revealed that, although there exist a number of strategies for the synthesis of isoxazolo [4,5-c]quinolines, [16][17][18][19] only two reports [20][21] of the synthesis of isoxazolo [4,3-c]quinolines exist, despite their significance as structural components of MRP-1 inhibitors. [22,23] Initially we reasoned that such an architecture could be generated from 3-(2-nitrophenyl)isoxazole-4-carboxylate by reduction of the nitro group to an amino group and subsequent cyclization with the carboxylate or formyl function.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the reduction of the nitro group would result in a 2-aminophenyl derivative, in which the amino group should readily undergo intramolecular cyclization with the keto moiety of the benzoyl group to furnish isoxazolo [3,4-c]quinoline. The rationale for such a strategy was based on reports by Rossi et al [16] on the synthesis of isoxazolo [4,5-c]quinolines from β-(2-aminophenyl)-α,β-ynones and Kaye et al…”
Section: Introductionmentioning
confidence: 99%